Identification of carboxypeptidase X (CPX)‐1 as a positive regulator of adipogenesis. Issue 7 (22nd March 2016) - Kim, Yu‐Hee; Barclay, Johanna L.; He, Jingjing; Luo, Xiao; O'Neill, Hayley M.; Keshvari, Sahar; Webster, Julie A.; Ng, Choaping; Hutley, Louise J.; Prins, Johannes B.; Whitehead, Jonathan P.
ABSTRACT: Adipose tissue expansion occurs through a combination of hypertrophy of existing adipocytes and generation of new adipocytes via the process of hyperplasia, which involves the proliferation and subsequent differentiation of preadipocytes. Deficiencies in hyperplasia contribute to adipose tissue dysfunction and the association of obesity with chronic cardiometabolic diseases. Thus, increased understanding of hyperplastic pathways may be expected to afford novel therapeutic strategies. We have reported that fibroblast growth factor (FGF)‐1 promotes proliferation and differentiation of human preadipocytes and recently demonstrated that bone morphogenetic protein and activin membrane‐bound inhibitor (BAMBI) is a central, proximal effector. Herein, we describe the identification and characterization of carboxypeptidase X (CPX)‐1, a secreted collagen‐binding glycoprotein, as a novel downstream effector in human primary and Simpson‐Golabi‐Behmel syndrome preadipocytes. CPX‐1 expression increased after treatment of preadipocytes with FGF‐1, BAMBI knockdown, or induction of differentiation. CPX‐1 knockdown compromised preadipocyte differentiation coincident with reduced collagen expression. Furthermore, preadipocytes differentiated on matrix derived from CPX‐1 knockdown cells exhibited reduced Glut4 expression and insulin‐stimulated glucose uptake. Finally, CPX‐1 expression was increased in adipose tissue from obese mice and humans. Collectively, these findings establish CPX‐1 as a positive regulator of adipogenesis situated downstream of FGF‐1/BAMBI that may contribute to hyperplastic adipose tissue expansion via affecting extracellular matrix remodeling.— Kim, Y.‐H., Barclay, J. L., He, J., Luo, X., O'Neill, H. M., Keshvari, S., Webster, J. A., Ng, C., Hutley, L. J., Prins, J. B., Whitehead, J. P. Identification of carboxypeptidase X (CPX)‐1 as a positive regulator of adipogenesis. FASEB J. 30, 2528‐2540 (2016). www.fasebj.org